The role of extracellular vesicles and interleukin-8 in regulating and mediating neutrophil-dependent cancer drug resistance - Zippoli, Mara; Ruocco, Anna; Novelli, Rubina; Rocchio, Francesca; Miscione, Martina Sara; Allegretti, Marcello; Cesta, Maria Candida; Amendola, Pier Giorgio (Frontiers in Oncology, 2022)
Tumor drug resistance is a multifactorial and heterogenous condition that poses a serious burden in clinical oncology. Given the increasing incidence of resistant tumors, further understanding of the mechanisms that make tumor cells able to escape anticancer drug effects is pivotal for developing new effective treatments. Neutrophils constitute a considerable proportion of tumor infiltrated immune cells, and studies have linked elevated neutrophil counts with poor prognosis. Tumor-associated neutrophils (TANs) can acquire in fact immunoregulatory capabilities, thus regulating tumor progression and resistance, or response to therapy. In this review, we will describe TANs’ actions in the tumor microenvironment, with emphasis on the analysis of the role of interleukin-8 (IL-8) and extracellular vesicles (EVs) as crucial modulators and mediators of TANs biology and function in tumors. We will then discuss the main mechanisms through which TANs can induce drug resistance, finally reporting emerging therapeutic approaches that target these mechanisms and can thus be potentially used to reduce or overcome neutrophil-mediated tumor drug resistance.